Effectiveness of curettage and bone grafting with and without elastic intramedullary nailing in the treatment of simple bone cyst in children: a meta-analysis - Li, Siyu; Wang, Lintao; Li, Yanan; Li, Shuai; Wang, Dan; Dong, Zhen (Frontiers in Surgery, 2025)
AimTo systematically evaluate the effectiveness of curettage and bone grafting with and without elastic intramedullary nailing in the treatment of simple bone cyst in children by analyzing domestic and international literature.MethodsSystematically search for literature comparing the efficacy of curettage and bone grafting with and without elastic intramedullary nailing in the treatment of simple bone cyst in children in databases such as Pubmed, Cochrane Library, Embase, CBM, CNKI, Wanfang, and VIP. Conduct quality assessment and data extraction of included literature and perform meta-analysis calculations using Stata12.0 software.ResultsMeta-analysis showed no heterogeneity (P = 0.581, I² = 0%). The cure rate was significantly higher in the EIN group (OR = 2.66, 95% CI = 1.48–4.77, P = 0.001) and 81% lower refracture incidence (OR = 0.19, 95% CI = 0.04–0.87, P = 0.032) vs. curettage alone.ConclusionCurettage and bone grafting with elastic intramedullary nailing is superior to curettage and bone grafting alone for treating simple bone cysts, with lower postoperative refracture incidence. Although the latter may require only one surgery theoretically, refracture or recurrence could necessitate 2–3 additional surgeries.